Best n-Term Approximations by Λ-Methods in the Spaces S_ϕ^p - Stepanets, O. I.; Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine the exact values of the upper bounds of n-term approximations of q-ellipsoids by Λ-methods in the spaces S_ϕ^p in the metrics of the spaces S_ϕ^p.